The right to mental health in the Brazilian prison system between 2018 and 2023 (International Seven Journal of Multidisciplinary, 2023)
This study analyzed the right to mental health in the Brazilian prison system between 2018 and 2023. It conducted a comprehensive literature review and an analysis of policies, programs and living conditions in the country's prisons. The results revealed a complex situation, with advances in expanding access to mental health services, early diagnosis of mental disorders and recognition of the importance of the issue. However, persistent challenges such as overcrowding, violence and lack of coordination between agencies were identified. It is concluded that it is essential to adopt an integrated approach, involving different government sectors, to ensure respect for human rights, the promotion of mental health and the effective reintegration of inmates into society.